2015
DOI: 10.1016/bs.pmbts.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A Game of Numbers

Abstract: The humoral response contributes to the protection against viral pathogens. Although antibodies have the potential to inhibit viral infections via several mechanisms, an ability to neutralize viruses directly may be particularly important. Neutralizing antibody titers are commonly used as predictors of protection from infection, especially in the context of vaccine responses and immunity. Despite the simplicity of the concept, how antibody binding results in virus inactivation is incompletely understood despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 121 publications
(179 reference statements)
1
22
0
Order By: Relevance
“…While the existence of a single serotype was suggested by conservation of E protein sequences among ZIKV strains, factors that define the sensitivity of flaviviruses to neutralization remain incompletely understood (Pierson and Diamond, 2015). A recent study of the functional complexity of DENV vaccine-immune sera demonstrated that changes at only two amino acids were sufficient to render DENV1 and DENV2 RVPs equally sensitive to neutralization by monovalent DENV1 immune sera (VanBlargan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While the existence of a single serotype was suggested by conservation of E protein sequences among ZIKV strains, factors that define the sensitivity of flaviviruses to neutralization remain incompletely understood (Pierson and Diamond, 2015). A recent study of the functional complexity of DENV vaccine-immune sera demonstrated that changes at only two amino acids were sufficient to render DENV1 and DENV2 RVPs equally sensitive to neutralization by monovalent DENV1 immune sera (VanBlargan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Humoral immune response plays a significant role in protection of the host from flavivirus infections (1). Generally, neutralizing antibodies are thought to be the key mediators of protection against flaviviruses following both infection and vaccination (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies can also exacerbate viral infection by different mechanisms that have long been described (55). In the vaccine context, infection by alpha-and flaviviruses (such as Dengue and Zika viruses) is enhanced when the antibody occupancy on the virion-surface epitopes falls below a critical threshold (56). This is the stoichiometric condition of an Fc-receptor-dependent form of ADE: the same antibodies that mediate ADE can be neutralizing and protective at higher occupancies on virions (56,57).…”
Section: Antibody-dependent Enhancement Of Infection (Ade)mentioning
confidence: 99%